Essential oil repellency in the management of honey harvesting of Apis mellifera L. (Research, Society and Development, 2022)
Essential oils are volatile substances extracted from different parts of plants and with different properties, among them the insecticidal or repellent action. The objective of this work was to test the essential oils of citronella (Cymbopogon nardus L.), copaiba (Copaifera sp.) and orange (Citrus sinensis L.) as alternative repellents on Apis mellifera L. An experimental bioassay was carried out with 320 captured bees, distributed in a 2x4 factorial design, where, factor 1: time; and factor 2: tested essential oils. An Entirely Randomized Design (DIC) was used, with 4 treatments (T) and 4 repetitions each, where T1: control (control); T2: citronella (C. nardus L.); T3: Copaíba (Copaifera sp.); and T4: Orange (C. sinensis L.). The results show that there is no significance in the tests performed; nor in relation to the interaction between the factors. However, according to the calculation of the Repellency Index (IR), there was a repellency effect among the evaluated oils. It is concluded that the essential oils of Copaifera sp, Citrus sinensis L. and Cymbopogon nardus L. show repellency over Apis mellifera L. with the highlight of the essential oil of C. nardus L.